Pandemic of perspectives : creative re-imaginings - Mehta, Rimple; Thakur, Sandali; Chakraborty, Debaroti (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book brings together academics, activists, health professionals, social work practitioners, poets, and artists from different parts of the world, during the COVID-19 pandemic, to record their visceral experiences and critical reflections. It sheds light on how the pandemic has exposed the inequities in society, and is shaping social institutions, affecting human relationships, and creating new norms with each passing day. It examines how people from diverse societies and fields of work have come to conceptualize and imagine a new world order based on the principles of social and ecological justice, care, and human dignity. It prioritises the realm of imagination, creativity, and affect in understanding social formations and in shaping societies beyond positivist approaches. Documenting the myriad experiences of and responses to the pandemic, the volume foregrounds varied processes of making meaning, understanding impulses, resistances, and coping mechanisms, and building solidarities. Further, it also acts as a tool of memory for future generations, and articulations- artistic, political, socio-cultural, scientific- of hope and perseverance. Its uniqueness lies in the way it brings together a much-needed interface between science, social sciences, and humanities. A compelling account on our contemporary lives, the volume will be of great interest to scholars of sociology and social anthropology, politics, art and aesthetics, psychology, literature, health and medical sciences"--
Keywords: COVID-19 Pandemic, 2020- -- Social aspects; COVID-19 (Disease) -- Social aspects; SOCIAL SCIENCE / General; POLITICAL SCIENCE / General; ART / General